EARLY COST-EFFECTIVENESS ANALYSIS OF NEW MEDICAL TESTS: RESPONSE. (3rd October 2016) - Smith, Alison Florence; Sutton, Andrew; Shinkins, Bethany
Abstract : As strong advocates and adopters of early cost-effectiveness modeling for test evaluation, we were excited to see the recent article "The Early Bird Catches the Worm: Early Cost-Effectiveness Analysis of New Medical Tests, " in which Buisman and colleagues present a succinct and generalizable framework for conducting this type of analysis. The authors have done an excellent job in identifying and summarizing the key components of this methodology, as well as highlighting fundamental differences between early analyses versus the traditional late-stage approach. As the number of medical tests coming to market continues to grow, there is an ever growing need to develop rigorous methodology in this area, and we commend the authors for this timely work.